Clinical and epidemiological characteristics of 369 patients with pelvic fractures in Eastern Zhejiang Province of China: a retrospective study - Jiao Dai; Junhong He; Ying Ying; Dichao Huang; Leling Feng (BMC Musculoskeletal Disorders, 2023)
Abstract Background Data on the epidemiological characteristics and prognostic factors of patients with pelvic fractures are lacking, particularly in China. This study aimed to summarise the clinical and epidemiological characteristics of patients with pelvic fractures in eastern Zhejiang Province, China, and to identify risk factors for poor prognosis. Methods The clinical data of 369 patients with pelvic fractures admitted to the Ningbo No. 6 Hospital between September 2020 and September 2021 were retrospectively analysed. Data on the demographic characteristics; fracture classification; injury time, cause, and site; treatment plan; and prognosis were collected using the Picture Archiving and Communication System and the Hospital Information System. Differences in constituent proportions were analysed using the chi-square test. Logistic regression analysis was used to identify factors affecting patient prognosis. Statistical significance was set at p ≤ 0.05. Results Among the 369 patients, there were 206 men and 163 women, at a ratio of 1.26:1, and the average age was 53.64 ± 0.78 years. More than 50% of patients were aged 41–65 years. The average length of hospital stay was 18.88 ± 1.78 days. The three most common causes of pelvic fractures were traffic accidents (51.2%), falls from height (31.44%), and flat-ground falls (14.09%). There were significant differences in the distribution of the three causes of injury depending on age (p < 0.001), sex (p < 0.001), and occupation (p < 0.0001). Most patients were manual workers (48.8%). Furthermore, most patients (n = 262, 71.0%) underwent surgical treatment for pelvic fractures. Postoperative complications occurred in 26 patients (7.05%), and infection was the main complication (73.08%). Age (p = 0.013), occupation (p = 0.034), cause of injury (p = 0.022), treatment options (p = 0.001), and complications (p < 0.0001) were independent factors affecting the prognosis of patients with pelvic fractures. One death (0.027%) occurred, which was due to severe blood loss. Conclusions Age, occupation, cause of injury, treatment options and complications were factors affecting patient prognosis. In addition, changes in blood flow and prevention of infection warrant attention.